Analysis of process factors of dry fermented salami to control Listeria monocytogenes - Enrico Novelli; Lucia Dal Santo; Stefania Balzan; Barbara Cardazzo; Dino Spolaor; Angiolella Lombardi; Lisa Carraro; Luca Fasolato (Italian Journal of Food Safety, 2017)
Challenge tests are a clear opportunity for manufacturers interested in the evaluation of their management system with the aim to reduce the spread of foodborne pathogens. This is a main concern especially in ready-to-eat food in relation to the risk associated with Listeria monocytogenes. For small and medium-scale food industry the manufacturing practices and products formulation are characterised by a wider variability and poor repeatability. The use of ad hoc challenge test and the comparison among different processing systems are strongly required. This paper reports a preliminary comparison among different challenge tests (n=12) commissioned by three manufacturers of raw-fermented salami during a period of three years (2013-2016). The challenge tests were designed to evaluate the growth potential (δ) of L. monocytogenes during the whole processing period of the salami. The doughs were prepared according to different formulations: the simplest formulation was represented by the use of salt, potassium nitrate, black pepper and starter cultures, while the most composited formulations also included the use of sugars and ascorbic acid in addition to nitrite salt. All the processing steps were conducted within an experimental laboratory dedicated for the processing of meat. After stuffing, the salami were dried and ripened under temperature and relative humidity control. The sugar inclusion can be considered as a protective factor, while the drying step at high temperature (above 20°C) was associated with higher δ values (δ>0.5 log10 cfu/g). The addition of starter cultures, and the subsequent acidification highlighted the importance of pH as the parameter able to affect the L. monocytogenes growth.